Javanese and Chinese Cultural Acculturation in the Development of Surakarta Batik and Peranakan Batik - Ruth Kiana Nuratri; Dian Yuni Pamuji; Clarosa Amanda Hasel (Universitas Negeri Semarang, 2026)
Batik is one of Indonesia's cultural heritages, recognized by UNESCO as an Intangible Cultural Heritage of Humanity in 2009. The development of Batik in Indonesia has been influenced not only by local cultures but also by interactions with various foreign cultures, including Chinese culture. These interactions gave rise to Peranakan batik, which developed primarily along Java's northern coast. This study aims to describe the forms of cultural acculturation found in Surakarta Batik and Peranakan Batik and to analyze the influence of Chinese culture on the development of batik motifs, colors, and philosophies in Indonesia. The study employed a qualitative descriptive method with a library research approach. Data were collected from books, journals, and relevant documents concerning the history of Batik, the Chinese Peranakan community, and the development of Batik culture in Java. The findings reveal that cultural acculturation is reflected in the use of Chinese-inspired floral and faunal motifs, such as the phoenix and liong (dragon), the application of vibrant colors in Peranakan batik, and the emergence of new batik creations that combine elements of Surakarta court batik with coastal aesthetic traditions. Go Tik Swan emerged as an important figure who successfully integrated Javanese and Chinese cultural elements in the creation of Indonesian Batik. This acculturation demonstrates that Batik is a dynamic cultural product that continues to evolve without losing its local identity.